Pengaruh Spritualitas Terhadap Motivasi Pasien Post Stroke Dalam Menjalani Fisioterapi Di Rumah Sakit - Nunung Febriany Sitepu; Ellyta Aizar; Asrizal Asrizal; Siti Zahara (Jurnal Kesehatan dan Fisioterapi, 2022)
Introduction: Spirituality includes an integrative energy in which it overcomes all human aspects and is a means to experience life. The benefits of spirituality can be in the form of hope, strength, and emotional support. Motivation is the force or impetus for a person to behave. Motivation is positive if the driving force is very strong, but without too much burden that causes excessive tension, so enough to cause a strong desire to move forward, characterized by behavior in participating in therapy. On the other hand, it is negative and inhibits if the urge is weak, reluctant, and lacks enthusiasm to join the physiotherapy program. Objective: to see how spirituality can affect the motivation of stroke patients in undergoing physiotherapy in hospitals. Method: descriptive analysis of the percentage with the aim of obtaining complete data quantitatively. The population in this study were 75 people who underwent physiotherapy at the hospital. Data was collected in May – October 2020. The instrument used was a spirituality and motivation questionnaire. Data analysis using the Exact Fisher test. Results: Based on Fisher's Exact test, the p value (0.000) < (0.05) means that there is an influence of spirituality on the motivation of stroke sufferers. Conclusion: The spiritual response for stroke sufferers in the implementation of spiritual motivation to recover shows an adaptive spiritual response or is increasingly positive seen from several aspects as follows: having realistic expectations (meaning confident that the illness will heal with support, attention, and affection from family and friends) people around).Keywords: spirituality, motivation, physiotherapy